Occurrence and genetic characterisation of Acanthamoeba spp. from environmental and domestic water sources in Queen Elizabeth Protected Area, Uganda. Issue 1 (December 2016) - Sente, Celsus; Erume, Joseph; Naigaga, Irene; Magambo, Phillip; Ochwo, Sylvester; Mulindwa, Julius; Namara, Benigna; Kato, Charles; Sebyatika, George; Muwonge, Kevin; Ocaido, Michael
Abstract Background Acanthamoeba is an emerging potentially pathogenic amoeba that has been receiving increasing attention worldwide as a reservoir and potential vector for the transmission of pathogenic bacteria. It is also associated with brain cell damage, keratitis and skin irritation in humans. Its effects are more severe in immunocompromised individuals. This study provides for the first time in Uganda, information on the prevalence and genotypes ofAcanthamoeba in environmental and domestic (tap) water. Methods A total of 324 environmental and 84 tap water samples were collected between November 2013 and September 2014. The samples were centrifuged, cultured (Non-Nutrient agar seeded with gram-negative bacteria) and observed under a microscope. After confirmation ofAcanthamoeba, genomic DNA was extracted for PCR assays by chemical lysis and purification with phenol/chloroform/isoamyl alcohol. Samples that showed the strongest positive bands (400–600 bp) were subjected to cycle sequencing. Results Among environmental and tap water samples, 107 (33 %) and 36 (42.9 %) tested positive forAcanthamoeba spp., respectively. Prevalence ofAcanthamoeba from specific environmental locations was as follows; Kazinga channel banks (60.7 %), Fish landing sites (50 %), River Kyambura (39.6 %) and Kazinga mid channel (5.3 %). There was a significant difference (p  = 0.001) in the prevalence ofAcanthamoeba between sampling sites. The mean (Mean ± SE) occurrence of the organism was higher in Kazinga channel banks (3.44 ± 0.49) and Fish landing sites (3.08 ± 0.53). Correlation between in situ parameters andAcanthamoeba was insignificant except for the Dissolved Oxygen (mg/ML) which was negatively correlated (r  = −0.231, p  = 0.001) toAcanthamoeba. Six distinct partialAcanthamoeba T-genotype groups T1, T2, T4, T5, T6 and T11 were obtained. Ultimately, Acanthamoeba spp., Acanthamoeba hatchetti andAcanthamoeba polyphaga were isolated in the current study. Conclusions There was a high prevalence ofAcanthamoeba in communal piped tap and environmental water used by communities, indicating poor environmental and domestic water quality.